2021
DOI: 10.1021/acs.est.0c07978
|View full text |Cite|
|
Sign up to set email alerts
|

Per- and Polyfluoroalkyl Substance (PFAS) Transport from Groundwater to Streams near a PFAS Manufacturing Facility in North Carolina, USA

Abstract: We quantified per-and polyfluoroalkyl substance (PFAS) transport from groundwater to five tributaries of the Cape Fear River near a PFAS manufacturing facility in North Carolina (USA). Hydrologic and PFAS data were coupled to quantify PFAS fluxes from groundwater to the tributaries. Up to 29 PFAS were analyzed, including perfluoroalkyl acids and recently identified fluoroethers. Total quantified PFAS (ΣPFAS) in groundwater was 20−4773 ng/L (mean = 1863 ng/L); the range for stream water was 426−3617 ng/L (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…Another study investigated transport of PFAS between groundwater and surface water, but was primarily focused on mass transfer rates. 24 The data presented here provide new information about the importance of the surface-water/groundwater boundary layer and its potential to drive temporal fluctuations in downgradient groundwater.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Another study investigated transport of PFAS between groundwater and surface water, but was primarily focused on mass transfer rates. 24 The data presented here provide new information about the importance of the surface-water/groundwater boundary layer and its potential to drive temporal fluctuations in downgradient groundwater.…”
Section: Resultsmentioning
confidence: 85%
“…PFAS-contaminated groundwater has been shown to contaminate surface waters, and vice versa in such systems. [22][23][24] For example, our prior work on Cape Cod, Massachusetts (MA), USA, characterized a contaminated groundwater plume that discharges to a groundwater-owthrough glacial kettle lake (Ashumet Pond). 6 Such glacial kettle lakes are common in northern latitudes and formed when blocks of glacial ice le behind by retreating ice sheets melted resulting in depressions (kettle holes) in the land surface that subsequently lled with water.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Extensive usage of PFAS over the past decades has resulted in unexpected environmental contamination. 5,18,19 A recent study 20 has revealed that groundwater near a PFAS manufacturing facility was contaminated by more than 20 different types of PFAS. Further, PFAS have been detected in drinking water systems [21][22][23] which has raised health concerns because they can accumulate in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…The continued presence of PFEA in the river is likely due at least in part to the discharge of PFAScontaminated groundwater to the Cape Fear River and its tributaried. Pétré et al (2021) showed that groundwater discharge to tributary streams of the Cape Fear River was a significant pathway for off-site migration of PFAS from the Fayetteville Works, with an estimated 32,000 g/year of PFAS discharged from groundwater to five small tributaries near the plant at baseflow. Stormwater runoff from the Fayetteville Works could also contribute to the presence of PFEA in the river; the role of PFAS desorption from river sediments should also be investigated (Harfmann et al 2021;Saleeby et al 2021).…”
Section: Mass Fluxesmentioning
confidence: 99%
“…The study was undertaken in the Cape Fear River watershed in North Carolina, USA, where drinking water intakes have had elevated PFAS concentrations. One of the major sources of PFAS contamination in the watershed is the Fayetteville Works, a fluorochemical manufacturing facility that emitted PFAS to air (D'Ambro et al 2021, Pétré et al 2021) and through direct discharge of process wastewaters to the Cape Fear River (Sun et al 2016a, Hopkins et al 2018 for about 4 decades. Other distributed sources of PFAS are also present in the watershed (Nakayama et al 2007), in particular in the Haw River sub-basin where PFSA and PFCA were detected from 2017-2019 at various water utilities (Herkert et al 2020).…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%